O frigorífico vacariense e os campos de cima da serra : políticas públicas e história econômica regional (1964-1997) - Almeida, Isabel Carneiro de (2008)
This research project is about a historical analysis of the Vacariense Frigorific S/A study, which was a big company, whose area was the slaughter of cattle ox in a big scale, cattle cutting and refrigeration to the commercialization, that was built in Campos de Cima Da Serra, in Vacaria city, Rio Grande Do Sul, in 1966 under the protection of the developed economy, characterized by the military dictatorship regime in Brazil, from 1964 to 1985. The work is done through the utilization of the verbal and business history, the history itself and image. Which has the objective of analizing the origin of its study and the existing relations between the history subjects and this vetor of the relations among the actors and its institutions in a scenery without any kind of work of individuals with specialization. The research shows some aspects from what happens in practic, when an economical interventionism model is administrated through the laws that guarantee the financial of the opening of new jobs and the distribution of food with the State intervention. Intending to explain the positive and negative points to the society by the aplication of this written model in the market protection and the intervention in the economy, having the consequences of its utilization. Dealing with politic, economic, social and cultural aspects, which involved the existence of friva and it was upheld for three decades as a social system, enterprising and stockist of jobs to the regional society. Preserving its visually material memory by a big amount of pictures. Showing its importance as a symbol of one time that the creation of cattle was the mainly economic activity in the region in which it became an icon in rise